Human Rights, the Rule of Law, and Development in Africa. - Zeleza, Paul Tiyambe (Pennsylvania Studies in Human Rights Ser., 2004)
Changes in human rights environments in Africa over the past decade have been facilitated by astounding political transformations: the rise of mass movements and revolts driven by democratic and developmentalist ideals, as well as mass murder and poverty perpetuated by desperate regimes and discredited global agencies. Human Rights, the Rule of Law, and Development in Africaseeks to make sense of human rights in Africa through the lens of its triumphs and tragedies, its uneven developments and complex demands. The volume makes a significant contribution to the debate about the connections between the protection of human rights and the pursuit of economic development by interrogating the paradigms, politics, and practices of human rights in Africa. Throughout, the essays emphasize that democratic and human rights regimes are products of concrete social struggles, not simply textual or legal discourses. Including some of Africa's leading scholars, jurists, and human rights activists, contributors to the volume diverge from Western theories of African democratization by rejecting the continental view of an Africa blighted by failure, disease, and economic malaise. It argues instead that Africa has strengthened and shaped international law, such as the right to self-determination, inspired by the process of decolonization, and the definition of the refugee. Insisting on the holistic view that human rights are as much about economic and social rights as they are about civil and political rights, the contributors offer novel analyses of African conceptions, experiences, and aspirations of human rights which manifest themselves in complex global, regional, and local idioms. Further, they explore the varied constructions of human rights in African and Western discourses and the roles played by states and NGOs in promoting or subverting human rights.Combining academic analysis with social concern, intellectual discourse with civic engagement, and scholarly research with institution building, this is a compelling and original approach to the question whether externally inspired solutions to African human rights issues have validity in a postcolonial world.